A Sociological Inquiry on Training and Treatment of the Wellbeing of Female Inmates in Correctional Facilities in Ogun and Lagos States, Nigeria - A. T Olawunmi; Ogunmefun Folorunsho M; Aiwuyuse Adesuwa L (RIRAI Publisher, 2023)
All over the world, the UNODC policy of 2011 agitates for needs to train, treat and promote the wellbeing of female inmates so as to reduce and control rate of recidivism in the country. Women are considered as care givers whose duty includes socialisation; domestication and procreation of offspring for societal continuity. In Nigeria, once women are convicted or apprehended by law, they faces lot of challenges ranging from stigmatization, poor health treatment, isolation, psychological trauma, unequal treatment among others Relevance publications to include local and international journals, magazines, newspaper, textbooks and articles were reviewed and double deviance feminist theory was adopted for justification of the inquiry. A mixed method was adopted with cross sectional survey method. Total population for the study in the three selected correctional facilities in Lagos and Ogun states was estimated to 348 inmates but 250 was found useful for the quantitative analysis while 15 female inmates were selected for the qualitative analysis. The result indicated that there are many factors that increase female involvement in criminal acts ranging from greed, poverty, unemployment. The second result shows that the treatment available for female inmates has insignificant negative effect on their wellbeing while the last indicated that training have significant relationship with female wellbeing in the facilities. The government, non-governmental organisation and the philanthropists should collective support the promotion of the wellbeing of female inmates and adequate cares and supervision should be ensure through the use of CCTV cameras in the facilities